Protection of Disappeared and Dead as a Result of War According to International Humanitarian Law and Islamic Law - Mirsa Astuti (International Journal Reglement & Society (IJRS), 2020)
In both Islamic law and International Humanitarian Law, war is an ultimum remedium (last resort) used to solve a problem after both parties cannot resolve their dispute or problem in a peaceful manner. This research was conducted using the normative legal research method. Based on the results of the research, it is known that international humanitarian law and Islamic law both provide protection for people who are involved in armed conflict, including people who have disappeared and died as a result of war. Persons involved in armed conflicts receive protection from international humanitarian law, as stipulated in Article 13 of the Geneva Convention 1949. Protected persons include combatants, militia and levee en maase members and civilians, but their protection has not been properly implemented, because there is still violence in every conflict. In Islam it is found in the Koran, Surat Al-Baqarah, verse 190; "And fight in the way of Allah those who fight against you, (but) do not cross the line, for verily Allah does not like those who transgress". Islam also prohibits attacks on non-combatants, Rasulullah SAW said: "Do not kill your parents, children and women" (H.R Abu Dawud)